Phase Transformations in Evaporated Ph‐BTBT‐10 Thin Films and Impact on the Device Performance - Fijahi, Lamiaa; Yan, Shunya; James, Ann Maria; Zhang, Min; Cazorla, Alba; Tamayo, Adrián; Li, Jinghai; Ocal, Carmen; Barrena, Esther; Resel, Roland; Mas‐Torrent, Marta (Advanced materials interfaces, 2025)
This paper reports on the phase transformation occurring in evaporated thin films of the organic semiconductor 2‐decyl‐7‐phenyl[1]benzothieno[3,2‐b][1]benzothiophene (Ph‐BTBT‐10), along with its impact on the performance of organic thin‐film field‐effect transistors (OFETs). Temperature‐dependent X‐ray reflectivity (XRR) studies reveal that the films crystallize in a single‐layer structure, which converts to a bilayer phase in the temperature range of 110°C –140°C; at further elevated temperatures, a liquid‐crystal phase is formed. The conversion of the as‐evaporated films to the bilayer structure is investigated by atomic force microscopy (AFM) and Kelvin probe force microscopy (KPFM) at specific annealing temperatures. The combination of XRR, AFM, and KPFM points out that only at the higher annealing temperature the phase transformation is completed. In a subsequent stage, the films are investigated as active layers in OFETs. An enhanced performance is observed in the annealed films with a higher mobility and reduced level of charge traps. The best electrical characteristics are realized when the bilayer transformation is fully accomplished. This paper investigates phase transformations in evaporated Ph‐BTBT‐10 thin films and their effect on OFET performance. X‐ray reflectivity and Force Microscopy investigations confirm full transformation from the single‐layer to the bilayer phase in the films annealed at 130°C, yielding improved OFET mobility and reduced charge traps.